Бамси Бейрек у контексті героїчної подорожі та процес навчання - Туба Салтик Озкан (Народна творчість та етнографія, 2010)
In this article the popular folk narrative, «Bay Büre Beg Oglı Bamsı Beyrek Boyı» in the Dede Korkut Book, is analyzed within the context of heroic adventure. The actions of the hero is considered with the universal formula of the initiation rituals. Bamsı Beyrek, after the extraordinary birth, started to journey as an initial adventure and returned to the starting point of the adventure, having been transformed in the end of the narrative. This journey occurs in a circular line. While the departure of the hero is the symbol of being grown up, the initiation part is the hard process of exams. And the way back home symbolizes the rebirth of the hero, by leaving his old life and entering the adult’s life.